2017
DOI: 10.4103/jmh.jmh_44_17
|View full text |Cite
|
Sign up to set email alerts
|

Education based on theory of planned behavior over sexual function of menopausal women in Iran

Abstract: Background:More than half of the sexual problems in menopausal women are due to insufficient knowledge or false beliefs about sexual function. Theory of planned behavior (TPB) is one of the important theories that explain the main process of adopting healthy behaviors. This study investigates the effect of education based on TPB over sexual function of menopausal women in Sabzevar, Iran.Materials and Methods:In this quasi-experimental study, the data were collected through a survey. This study included 180 Ira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Then the educational program that was designed based on the TPB constructs was implemented for the intervention group, using methods of lecture giving, group discussion, question and answer, role-playing, slide show, and pamphlet distribution, during three sessions of 110 minutes duration. Education time and sessions had a wide variation among different studies [28][29][30]35].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then the educational program that was designed based on the TPB constructs was implemented for the intervention group, using methods of lecture giving, group discussion, question and answer, role-playing, slide show, and pamphlet distribution, during three sessions of 110 minutes duration. Education time and sessions had a wide variation among different studies [28][29][30]35].…”
Section: Methodsmentioning
confidence: 99%
“…The two groups were asked to fill TPB question-naire again, once immediately after the intervention and then one month after the educational program. In previous studies, different times (from 1 month to three months) have been used to assess the change in TPB constructs [28][29][30]35]. In this study, only the statistician was blinded to the allocation of the study groups.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of most studies are based on the principle that training based on theories can have a positive effect on increasing the capabilities of menopausal women and improving their sexual function. Based on these studies, it has been shown that the planned behavior model is suitable for education in the field of menopause [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%